EFFECT OF THE CERVICAL ENDURANCE TRAINING PROGRAMME IN MECHANICAL NECK PAIN (International Journal of Physiotherapy, 2014)
Background: Mechanical neck pain commonly arises insidiously and is generally multifactorial in origin. Regardless of the primary source of pain, the prognosis for individual experiencing chronic neck pain is poor. Exercise interventions are important for effective management of patients with neck pain.the objective of the study is to compare the efficacy of cervical endurance training programme with cervical isometric exercise in alleviating symptoms of mechanical neck pain.Methods: 40 subjects were assessed and identified with Mechanical Neck Pain and recruited for the study and were randomly divided into two groups. In one group endurance training for cervical muscles and in another group resisted isometric had been given for 3 weeks. The post treatment scores regarding endurance, pain intensity, disability, Range of motion and muscle power were compared with the pre treatment scores.Results: Paired‘t’ test was done to compare the pretreatment scores with the post treatment scores .Unpaired ‘t’ test was done to compare the post treatment scores of both the groups. The pain intensity, disability were found to be significantly decreased in experimental group than the control group (p